Esophageal Stenting: How I Do It - Rui Silva (GE: Portuguese Journal of Gastroenterology, 2023)
Endoscopic esophageal stent placement is an effective palliative treatment for malignant strictures and has also been successfully used for benign indications, including esophageal refractory strictures and iatrogenic leaks and perforations. Despite several decades of evolution and the wide variety of esophageal stents available to choose from, an ideal stent that is both effective and without adverse events such as stent migration, tissue ingrowth, or pressure necrosis has yet to be developed. This paper is an overview of how this evolution happened, and it also addresses the characteristics of some of the currently available stents, like their material and construction, delivery device, radial and axial force pattern, covering and size which may help to understand and avoid the occurrence of adverse events. The insertion delivery systems and techniques of placement of an esophageal self-expandable metal stent are reviewed, as well as some tips and tricks regarding placement and management of adverse events.